1991
DOI: 10.1111/j.1365-2249.1991.tb02964.x
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin enhances T cell function by modulating interleukin activities

Abstract: SUMMARYCiprofloxacin (ClP)isa quinolonccarboxylicacid derivative with a broad spectrum of antibacterial activity. CIP (01-30 /jg/ml) enhanced DNA synthesis of mouse spleen eells and human peripheral blood lymphocytes (PBL) that had been activated with T eell mitogens or with alloaiitigens. In addition, CIP increased thc amount of IL-2 found in thc supernatants of phylohaemagglutinin (PHA)-stimulated human PBL, The presence of CIP in the medium ({)-3-IO /(g/ml) increased the levels of IL-1 found in Ihe eulture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
3
30
0
1
Order By: Relevance
“…In contrast, there was no effect on IL-1 release in the same experimental setting (33). Because the effect of quinolones on cytokine synthesis is not consistent and differs by the cell type and the cytokine examined (13), it is tempting to speculate that the cytokine response to drug treatment is cell type specific and influenced by the microenvironment under which cells exist.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, there was no effect on IL-1 release in the same experimental setting (33). Because the effect of quinolones on cytokine synthesis is not consistent and differs by the cell type and the cytokine examined (13), it is tempting to speculate that the cytokine response to drug treatment is cell type specific and influenced by the microenvironment under which cells exist.…”
Section: Discussionmentioning
confidence: 65%
“…An in vitro study performed on phagocytes obtained from pigs showed that enrofloxacin may accumulate in phagocytes, and this way it may lead to an increase in their bactericidal properties (18). Khalifeh et al (7) reported that enrofloxacin targeted the humoral immune response in chickens, and resulted in a decrease in antibody production after vaccination during antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…At concentrations of 1.6 to 50 ,ug/ml, fluoroquinolones cause a significant increase in the uptake of [3H]thymidine into the DNA of mitogen-stimulated human peripheral blood lymphocytes (PBLs) (3,(6)(7)(8)29). The mechanism responsible for the increased thymidine incorporation by fluoroquinolone-treated PBLs is unknown.…”
mentioning
confidence: 99%
“…The mechanism responsible for the increased thymidine incorporation by fluoroquinolone-treated PBLs is unknown. Moreover, we and others have recently reported interleukin-2 (IL-2) production to be markedly increased in phytohemagglutinin (PHA)-stimulated PBLs incubated in the presence of fluoroquinolones (21,23,29,32), the increase being due to enhanced IL-2 transcription and the resulting higher levels of IL-2 mRNA (22,25). Parallel to that of IL-2, increased gamma interferon (IFN-y) production has been detected in PBL cultures incubated with ciprofloxacin or ofloxacin (11,24,32).…”
mentioning
confidence: 99%